THE ROLE OF WOMEN IN FOOD SECURITY OF THE BADUY COMMUNITY IN THE ERA OF GLOBALIZATION AND MEDIA CONVERGENCE - Najmudin Najmudin; Ima Maisaroh; Nina Yuliana (Marwah: Jurnal Perempuan, Agama dan Jender, 2022)
Baduy women have a special and honorable position because they are directly related to the concept of Ambu and Nyi Pohaci (the Goddess of Rice) as the goddess of the source of Baduy life. With this identification, the food security of the Baduy family and community is determined by the role of women. The need for agricultural land/fields continues to be urgent, slowly among them in 2010-2012 the Baduy people were able to buy land outside of customary land covering an area of 900 hectares spread over 12 sub-districts designated as agricultural land expansion. Land expansion is needed to meet food availability as well as family economic income which has an impact on increasing welfare. The land is purchased from years of savings from financial management and women's creative industries. This study aims to determine the method/model of the role of Baduy women in food security for families and communities through qualitative research with activity theory and religious communication. The result is that Baduy women continue to use their traditional positions and roles by utilizing customary knowledge and skills which continue to be developed with concessions to the interpretation of customary law and are carried out according to social and economic motives to return to the big motive, namely the religious motive to buy land and carry out functions. worship as a farmer and the concept of Sunda Wiwitan belief.